High-resolution and broadband mid-infrared Zeeman spectrum of gas-phase nitric oxide using a quantum cascade laser around 5.2 μm. (13th January 2017) - Wu, Kuijun; Liu, Linmei; Chen, Zhenwei; Cheng, Xuewu; Yang, Yong; Li, Faquan
Abstract: A broadly tunable single-mode quantum cascade laser operating around 5.2 μ m has been used to study the high-resolution and broadband mid-IR Zeeman spectrum of Gas-phase 14 N 16 O. The Zeeman spectrum signals in the R (from R0.5 to R22.5 ), Q (from Q0.5 to Q6.5 ) and P (from P1.5 to P14.5 ) branches of the fundamental vibrational transition, X Π 1 / 2 2, X Π 3 / 2 2 ( v = 1 ← 0 ), have been recorded with both large spectral region (over the range of 1824 –1947 cm −1 ) and high spectral resolution (<0.001 cm −1 ) for the first time. We simulated the patterns of magnetic Zeeman split lines in the R, Q, and P branches, and calculated the Landé g -factor g J of the Π 1 / 2 2 and Π 3 / 2 2 components for pure Hund's coupling case (a) and (b), and intermediate coupling (a–b) case. The experimental Zeeman spectrum measured at various values of magnetic field strength (from 0.04 to 0.32 T) at conditions of both B ⊥ E and B ∥ E was calibrated by a 101.6 mm long solid germanium etalon with a free spectral range (FSR) of 0.012 cm −1 . Good agreement between the calculated Landé g -factors using Radford's theory and their best fit values inferred from the experimental data was obtained, which suggests that the Landé g -factor in Hund's coupling case (a–b) is a better approximation, either at higher rotational quantum numbers, or at lower rotational levels, for both Π 1 / 2 2 and Π 3 / 2 2 subsystems. Our results provide a more general evidence to determine the coupling case of NO than previously available, because we can measure and simulate the high-resolution and broadband mid-IR Zeeman spectrum for both low and high rotational levels of the two subsystems.